2010
DOI: 10.1186/1471-2407-10-152
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with initial treatment and survival for clinically localized prostate cancer: results from the CDC-NPCR Patterns of Care Study (PoC1)

Abstract: BackgroundDespite the large number of men diagnosed with localized prostate cancer, there is as yet no consensus concerning appropriate treatment. The purpose of this study was to describe the initial treatment patterns for localized prostate cancer in a population-based sample and to determine the clinical and patient characteristics associated with initial treatment and overall survival.MethodsThe analysis included 3,300 patients from seven states, diagnosed with clinically localized prostate cancer in 1997.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
4
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 42 publications
6
57
4
1
Order By: Relevance
“…[11][12][13][14][15] However, our findings are plausible since a single comorbid condition at the time of treatment may not seem overly concerning for a dismal prognosis. In fact, upon a more thorough review of the extant literature, one discovers that others also failed to find a significant difference in the treatment rate when comparing men with a Charlson Score of 1 or 2 vs. 0.…”
Section: Discussioncontrasting
confidence: 40%
“…[11][12][13][14][15] However, our findings are plausible since a single comorbid condition at the time of treatment may not seem overly concerning for a dismal prognosis. In fact, upon a more thorough review of the extant literature, one discovers that others also failed to find a significant difference in the treatment rate when comparing men with a Charlson Score of 1 or 2 vs. 0.…”
Section: Discussioncontrasting
confidence: 40%
“…This is similar to the trends reported by NCI SEER outcomes (45% radical prostatectomy, 24% total radiation, 8% hormonal, and 9% watchful waiting) 31 and within the regional trends reported by the Centers for Disease Control and Prevention (CDC) National Program of Cancer Registries (NPCR) Patterns of Care (PoC1) study. 32 Once prostate cancer was detected, we also observed a decrease in the age of surgery with successive decades, with the average age of surgical intervention as early as 63 years for the current decade and more conservative treatment likely for older age at cancer diagnosis. This trend has been observed elsewhere around the United States.…”
Section: Discussionmentioning
confidence: 88%
“…24,27,33 The PoC1 study also found that age at diagnosis affected the likely treatment choice, with older patients more likely to receive conservative treatment and younger individuals more likely to receive radical prostatectomies. 32 Single institution treatment trends, such as at Yale University, also reported a disparity in the ages of individuals receiving radical prostatectomy versus radiation implant treatment, with younger individuals receiving prostatectomy. 34 Comparing radical prostatectomy and radiation treatment outcomes was challenging, as we had few documented prostate cancer deaths in our population.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] It has been demonstrated that AA race, being unmarried, and having public/no insurance are associated with receiving nondefinitive treatment; and, among those who do receive definitive therapy, AA race and being unmarried are associated with receiving RT over RP. 13 Overall survival, however, was associated with undergoing RP, younger age, and being married, among other factors. An additional consideration is whether all men with low-risk disease even require aggressive treatment.…”
Section: Low Riskmentioning
confidence: 97%